Amino Acid‐Sensing Neurons in the Anterior Piriform Cortex Control Brown Adipose Tissue Thermogenesis - Peixiang Luo; Kexin Tong; Yeting Gan; Min Tang; Yuguo Niu; Kan Liu; Shihong Ni; Shangming Wu; Xiaoxue Jiang; Haizhou Jiang; Fei Xiao; Shanghai Chen; et al. (Advanced Science, 2025)
Abstract Amino acid sensing in the central nervous system plays a key role in regulating energy homeostasis. The anterior piriform cortex (APC) has been implicated in sensing amino acid deficiency and rapidly inducing an aversive response. However, the precise types of neurons involved and whether they possess additional metabolic regulatory functions remain to be elucidated. The study reveals that corticotropin‐releasing hormone (CRH) neurons in the APC (APCCRH neurons) are activated by a leucine‐deficient diet to modulate brown adipose tissue thermogenesis and that they regulate body temperature in response to leucine deprivation. The findings reveal that APCCRH neurons are sensitive to leucine‐deprivation signaling, with general control nonderepressive‐2 playing an essential role in enhancing their intrinsic excitability. Furthermore, APCCRH neurons project into the known hypothalamic thermoregulatory region of the lateral hypothalamus, and APCCRH–lateral hypothalamus circuits mediate leucine deprivation‐induced thermogenesis. Additionally, it is observed that thermogenic regulation by APCCRH neurons contributes to the maintenance of body temperature under cold exposure. Collectively, the findings identify a population of leucine‐sensing APCCRH neurons, and reveal the signals and circuits involved in their regulation of brown adipose tissue thermogenesis and their subsequent contribution to body temperature regulation and energy homeostasis.